Penatalaksanaan pemeriksaan mammografi pada kasus kanker payudara dengan modalitas computed radiography - Adela, Natri; Utama, Harry Wahyudhy; Utami, Muslimah Putri; Zanariah, Zanariah (JOURNAL of Public Health Concerns, 2026)
Background: Breast cancer (carcinoma mammae) is a major global health problem with increasing incidence, making early detection essential to reduce mortality. Mammography is proven effective for both screening and diagnostic purposes, using standard projections such as cranio-caudal (CC) and medio-lateral oblique (MLO), with additional variations to enhance sensitivity. The transition from analog to digital systems through computed radiography (CR) enables image storage, analysis, and integration with picture archiving and communication system (PACS), although its resolution is lower than digital radiography (DR). Success in examination depends not only on technology but also on radiographer competence in positioning, compression, and exposure parameter settings. Thus, the implementation of CR at Siloam Sriwijaya Hospital Palembang is a strategic step in providing modern, effective, and standardized diagnostic services to support accurate diagnosis of carcinoma mammae. Purpose: To evaluate the management of mammography examinations in carcinoma mammae cases using computed radiography (CR) at the Radiology Department of Siloam Sriwijaya Hospital Palembang, and to assess the conformity of procedures with operational standards as well as the quality of images produced in supporting diagnostic accuracy. Method: This study was conducted in 2026 at the Radiology Department of Siloam Sriwijaya Hospital Palembang, South Sumatra, using a descriptive case study approach. The subject was a female patient suspected of having carcinoma mammae, selected through purposive sampling. Examinations were performed using computed radiography (CR) with available mammography units. Data were collected through direct observation of examination stages, interviews with radiographers, and documentation including notes, examination images, and activity records. Results: The mammography examination with CR on a female patient suspected of carcinoma mammae revealed an irregular, spiculated, high-density mass measuring approximately 4.19 × 3.94 × 3.39 cm in the upper outer quadrant of the left breast, accompanied by fibroglandular architectural distortion and multiple enlarged lymph nodes in the left axilla. Examinations using CC and MLO projections produced diagnostic-quality images despite the nipple not appearing in profile, with overall image quality consistent with theoretical and practical standards. Conclusion: Mammography examinations using CR in carcinoma mammae cases at Siloam Sriwijaya Hospital Palembang were conducted according to radiology procedures. The use of CC and MLO projections provided optimal visualization of breast tissue, with images meeting diagnostic criteria of sharpness, density, contrast, and anatomical detail, thereby supporting accurate diagnosis of carcinoma mammae. Suggestion: The quality of mammography services using CR should be continuously maintained and improved through regular training for radiographers and healthcare personnel. Comparative studies between CR and digital radiography (DR) are also recommended to evaluate differences in image quality and effectiveness, thereby supporting the enhancement of diagnostic standards more optimally. Keywords: Breast cancer; Computed radiography; Mammography; Radiographic management Pendahuluan: Kanker payudara (carcinoma mammae) merupakan masalah kesehatan utama dengan angka kejadian yang terus meningkat, sehingga deteksi dini menjadi strategi penting dalam menurunkan mortalitas. Mammografi terbukti efektif sebagai metode pencitraan untuk skrining maupun diagnostik, dengan proyeksi standar seperti cranio-caudal (CC) dan medio-lateral oblique (MLO), serta variasi tambahan untuk meningkatkan sensitivitas. Perkembangan teknologi dari sistem analog menuju digital melalui computed radiography (CR) memungkinkan penyimpanan citra, analisis, dan integrasi dengan picture archiving and communication system (PACS), meskipun resolusinya lebih rendah dibandingkan digital radiography (DR). Keberhasilan pemeriksaan tidak hanya bergantung pada teknologi, tetapi juga pada kompetensi radiografer dalam melakukan positioning, kompresi, dan pengaturan parameter eksposi. Oleh karena itu, implementasi CR di RS Siloam Sriwijaya Palembang menjadi langkah strategis dalam menyediakan layanan diagnostik yang modern, efektif, dan sesuai standar untuk mendukung akurasi diagnosis kasus kanker payudara. Tujuan: Mengetahui penatalaksanaan pemeriksaan mammografi pada kasus kanker payudara dengan menggunakan modalitas computed radiography (CR) di Instalasi Radiologi Rumah Sakit Siloam Sriwijaya Palembang, sehingga dapat memberikan gambaran mengenai kesesuaian prosedur dengan standar pelaksanaan serta kualitas citra yang dihasilkan dalam mendukung akurasi diagnosis. Metode: Kegiatan dilaksanakan pada tahun 2026 di Instalasi Radiologi Rumah Sakit Siloam Sriwijaya Palembang, Sumatera Selatan, dengan pendekatan deskriptif studi kasus. Subjek penelitian adalah seorang pasien perempuan dengan dugaan kanker payudara yang dipilih melalui teknik purposive sampling. Pemeriksaan dilakukan menggunakan modalitas computed radiography (CR) dengan unit mammografi yang tersedia, sedangkan data diperoleh melalui observasi langsung terhadap tahapan pemeriksaan, wawancara dengan radiografer, serta dokumentasi berupa catatan, foto hasil pemeriksaan, dan kegiatan selama proses berlangsung. Hasil: Pemeriksaan mammografi dengan modalitas computed radiography (CR) pada pasien Ny. X dengan dugaan kanker payudara di RS Siloam Sriwijaya Palembang menampilkan massa iregular bertepi tidak tegas, spikulata, dan berdensitas tinggi, pada kuadran atas luar payudara kiri, disertai distorsi arsitektur jaringan fibroglandular serta pembesaran kelenjar bening multipel di aksila kiri. Pemeriksaan menggunakan proyeksi cranio-caudal (CC) dan medio-lateral oblique (MLO) menghasilkan citra yang memenuhi kriteria diagnostik meskipun nipple tidak tampak dalam profil, pemeriksaan menghasilkan citra yang optimal sesuai teori maupun praktik. Simpulan: Pemeriksaan mammografi dengan modalitas computed radiography (CR) pada kasus kanker payudara telah sesuai dengan prosedur radiologi. Pemeriksaan menggunakan proyeksi cranio-caudal (CC) dan medio-lateral oblique (MLO) mampu menampilkan jaringan payudara secara optimal, dengan citra yang memenuhi kriteria diagnostik berupa ketajaman, densitas, kontras, dan detail anatomi yang jelas, sehingga mendukung akurasi diagnosis kanker payudara. Saran: Mutu pelayanan pemeriksaan mammografi dengan modalitas computed radiography (CR) diharapkan dapat terus dipertahankan dan ditingkatkan melalui pelatihan berkala bagi radiografer serta tenaga kesehatan, serta dilakukan penelitian komparatif dengan digital radiography (DR) untuk menilai perbedaan kualitas citra dan efektivitasnya, sehingga dapat mendukung peningkatan standar diagnostik secara lebih optimal.